Odpowiedzi

Najlepsza Odpowiedź!
2009-12-01T18:44:33+01:00
A)
x/2 + y/3 = 1 1/3 | 2
x/3 - y/2 = 2 1/3 | (-3)

x+ 2y/3 = 2 2/3
-x + 3y/2 = -7

2y/3 +3y/2 = - 4 1/3
4y+9y/6 = -4 1/3

13y/6= - 4 1/3 | 6
13y = - 26 |13
y= -2

x+2y/3 = 2 2/3
x + (-4/3) = 2 2/3
x- 4/3 = 2 2/3
x= 8/3 + 4/3
x= 12/3
x= 4

y= -2
x=4


b)
3/5 x+1/2 y= 2
12 (2x-y) = 2

3/5x + 1/2y = 2
x- 1/2 y =2

1 3/5 x= 4
8/5x= 4 | 5/8 (mnoże razy odwrotność tego co mam przy x)
x=20/8
x=1 1/2

x- 1/2y =2
1 1/2 - 1/2 y=2
-1/2 y= 2- 1 1/2 | -1/2
y= -1

x=1 1/2
y= -1


8 2 8
2009-12-01T18:46:34+01:00
B) 0,6x+0,5y=2
x-y=2/*0,5
0,6x+0,5y=2
0,5x-0,5y=1
1,1x=3/:1,1
x=2,72
0,6x+0,5y=2
0,6*2,72+0,5y=2
1,63+0,5y=2
0,5y=2-1,63
0,5y=0,36/:0,5
y=0,72
3 3 3